Late onset systemic lupus erythematosus-associated protein-losing enteropathy: a case report and literature review. (2nd January 2019) - Fukunaga, Kentaro; Yamaguchi, Masafumi; Yoshihashi, Saiko; Murayama, Tsunetaka; Iriyama, Tomoko; Kanda, Rie; Nagao, Taishi; Fujimoto, Noriki; Nakano, Yasutaka
Abstract: The incidence of late onset systemic lupus erythematosus (SLE) is reportedly low. Moreover, it is rare for late onset SLE to be complicated with protein-losing enteropathy (PLE). We herein report on a 71-year-old Japanese woman with bilateral pleural effusion in whom the finding of hypoalbuminemia confirmed the diagnosis of PLE with late onset SLE. She was initiated on methylprednisolone and intravenous cyclophosphamide. Despite switching from cyclophosphamide to azathioprine and tapering methylprednisolone, remission has been sustained for several years. Our review of published case reports on late onset SLE-associated PLE indicate that this disease is more common among Asians than other ethnicities, and is often resistant to treatment with corticosteroid monotherapy. Furthermore, anti- U1-ribonucleoprotein antibody may be a risk factor of PLE in late onset SLE patients. Although PLE is an uncommon manifestation of late onset SLE, clinicians must be aware that it can develop in patients with late onset SLE.